Measuring mistreatment of women throughout the birthing process: implications for quality of care assessments. Issue 53 (27th August 2018) - Abuya, Timothy; Sripad, Pooja; Ritter, Julie; Ndwiga, Charity; Warren, Charlotte E
Abstract: Measuring mistreatment and quality of care during childbirth is important in promoting respectful maternity care. We describe these dimensions throughout the birthing process from admission, delivery and immediate postpartum care. We observed 677 client–provider interactions and conducted 13 facility assessments in Kenya. We used descriptive statistics and logistic regression model to illustrate how mistreatment and clinical process of care vary through the birthing process. During admission, the prevalence of verbal abuse was 18%, lack of informed consent 59%, and lack of privacy 67%. Women with higher parity were more likely to be verbally abused [AOR: 1.69; (95% CI 1.03, 2.77)]. During delivery, low levels of verbal and physical abuse were observed, but lack of privacy and unhygienic practices were prevalent during delivery and postpartum (>65%). Women were less likely to be verbally abused [AOR: 0.88 (95% CI 0.78, 0.99)] or experience unhygienic practices, [AOR: 0.87 (95% CI 0.78, 0.97)] in better-equipped facilities. During admission, providers were observed creating rapport (52%), taking medical history (82%), conducting physical assessments (5%). Women's likelihood to receive a physical assessment increased with higher infrastructural scores during admission [AOR: 2.52; (95% CI 2.03, 3.21)] and immediately postpartum [AOR 2.18; (95% CI 1.24, 3.82)]. Night-time deliveries were associated with lower likelihood of physical assessment and rapport creation [AOR; 0.58; (95% CI 0.41, 0.86)]. The variability of mistreatment and clinical quality of maternity along the birthing process suggests health system drivers that influence provider behaviour and health facility environment should be considered for quality improvement and reduction of mistreatment.